Inside Risks: The Foresight Saga, Redux. - Neumann, Peter G. (Communications of the ACM, 2012)
The author discusses strategies for risk reduction in computing, focusing on the balance between short-term optimization and long-term security and functionality in computer software and hardware, networks, and information systems. He presents recommendations to enable short-term innovation as well as long-term stability, including strengthening and standardizing security and reliability requirements, promoting experimental computer science and engineering research, and formal assurance methods.